Repeatability and validity of a standardised maximal step-up test for leg function-a diagnostic accuracy study - Wändell Per (BMC Musculoskeletal Disorders, 2011)
Abstract Background Objectively assessed physical performance is a strong predictor for morbidity and premature death and there is an increasing interest in the role of sarcopenia in many chronic diseases. There is a need for robust and valid functional tests in clinical practice. Therefore, the repeatability and validity of a newly developed maximal step up test (MST) was assessed. Methods The MST, assessing maximal step-up height (MSH) in 3-cm increments, was evaluated in 60 healthy middle-aged subjects, 30 women and 30 men. The repeatability of MSH and the correlation between MSH and isokinetic knee extension peak torque (IKEPT), self-reported physical function (SF-36, PF), patient demographics and self-reported physical activity were investigated. Results The repeatability between occasions and between testers was 6 cm. MSH (range 12-45 cm) was significantly correlated to IKEPT, (r = 0.68, P < 0.001), SF-36 PF score, (r = 0.29, P = 0.03), sex, age, weight and BMI. The results also show that MSH above 32 cm discriminates subjects in our study with no limitation in self-reported physical function. Conclusions The standardised MST is considered a reliable leg function test for clinical practice. The MSH was related to knee extension strength and self-reported physical function. The precision of the MST for identification of limitations in physical function needs further investigation.